FEMALE IMAM AND KHATIB: The Progressive Tradition of Gender-Responsive Practices in Balingka, West Sumatera (JOURNAL OF INDONESIAN ISLAM, 2017)
The practice of allowing women to be the imam and khatib for Eid prayer in Balingka has become a long tradition for more than a century. The simple way of thinking, the topographic problem, and the intention to form united community have allowed this tradition to be still practiced today. In reality, such tradition has never been mentioned in the classic fiqh (Islamic jurisprudence). In fact, allowing women to be the imam and khatib in Eid prayer never occurs in Islamic community from other regions. To reach the goal of silaturrahim (the bond of friendship) between the local settlers and perantau (local people who live or work in other regions) also contribute to the perseverance of this tradition. This practice serves as the intermediary between the tendencies of fanaticism of traditional Islam and the radical religious changes offered by liberal Islam. Unknowingly, this practice, which is started from the small village, and inspired from the simple way of thinking, has implemented the notion of gender equality that promoted by the group of progressive Islam.